HUBUNGAN ANTARA STATUS KLINIKOPATOLOGIS PADA PENDERITA KANKER PAYUDARA LANJUT LOKAL YANG MENJALANI MASTEKTOMI RADIKAL MODIFIKASI PASCA KEMOTERAPI NEOAJUVANT DENGAN KEJADIAN METASTASIS JAUH - , I. ANDI TEJO SAMPURNA, dr. Kunta Setiadji, SpB(K)Onk. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Breast cancer is currently ranked the second most common cancers and cancer ranked first in women. The incidence of locally advanced breast cancer (LABC) in Indonesia is considerably high, between 40% - 80%, with distant metastases rate about 62,5% whereas mortality rate in LABC from 12% - 37% caused by distant metastases of cancer after surgery and chemotherapy. The development of distant metastases can be affected by clinicopathologic factors and its treatment. Goals : To find the correlation and strength of clinicopathologic characteristics in patients with LABC who underwent modified radical mastectomy after neoadjuvant chemotherapy with the incidence of distant metastases. Subjects : Breast cancer patients who underwent modified radical mastectomy after neoadjuvant chemotherapy in Dr Sardjito Hospital from January to December 2010. Methods : This was a retrospective cohort study. The statistical test used was chi-squared for univariate analysis and logistic regression for multivariate analysis. Results : The number of subjects in this study is 84 patients with LABC, age group less than 40 years old there were 14 patients (16,7%), equal or greater than 40 years old were 70 patients (83,3%). Tumor size found at most was greater or equal to 5 cm, in 58 patients (69,0%). Clinical stage found at most was IIIA in 54 patients (64,3%), and stage III in 43 patients (51,2%), lymph nodes involved number was 1-3 in 47 patients (56%). The immunohistochemical subtype luminal A, luminal B, triple negative, and HER-2 overexpression was found in 49 (58,3%), 7 (8,3%), 11 (13,1%) and 17 patients (20,2%), respectively. Recurrence was developed in 16 patients (19%), and distant metastases was found in 11 patients (13,1%) which consisted of bone metastases 6 patients (54,5%) from subtype Luminal A 4 patients, lung metastases 4 (36,4%) from subtype Luminal A 3 patients, and brain metastases was found in 1 patient with subtype Luminal A as well (9,1%). In this study, recurrence status was the statistically significant result (p=0,000), and based on the logistic regression test, recurrence status was a predictor factor with distant metastases tendency 22 times higher compared with other factors. Conclusion : Recurrence status is correlated with distant metastases and predict distant metastases 22 times compared to other factors. Keywords : clinicopathologic status, recurrence status, locally advanced breast cancer, modified radical mastectomy, neoadjuvant chemotherapy, distant metastases.